3D bioprinted white adipose model for in vitro study of cancer-associated cachexia induced adipose tissue remodeling. (1st July 2022) - Xue, Wen; Yu, Seok-Yeong; Kuss, Mitchell; Kong, Yunfan; Shi, Wen; Chung, Soonkyu; Kim, So-Youn; Duan, Bin
Abstract: Cancer-associated cachexia (CAC) is a complex metabolic and behavioral syndrome with multiple manifestations that involve systemic inflammation, weight loss, and adipose lipolysis. It impacts the quality of life of patients and is the direct cause of death in 20%–30% of cancer patients. The severity of fat loss and adipose tissue remodeling negatively correlate with patients' survival outcomes. To address the mechanism of fat loss and design potential approaches to prevent the process, it will be essential to understand CAC pathophysiology through white adipose tissue models. In the present study, an engineered human white adipose tissue (eWAT) model based on three-dimensional (3D) bioprinting was developed and induced with pancreatic cancer cell-conditioned medium (CM) to mimic the status of CAC in vitro . We found that the CM induction significantly increased the lipolysis and accumulation of the extracellular matrix (ECM). The 3D eWATs were further vascularized to study the influence of vascularization on lipolysis and CAC progression, which was largely unknown. Results demonstrated that CM induction improved the angiogenesis of vascularized eWATs (veWATs), and veWATs demonstrated decreased glycerol release but increased UCP1 expression, compared to eWATs. Many unique inflammatory cytokines (IL-8, CXCL-1, GM-CSF, etc) from the CM were detected and supposed to contribute to eWAT lipolysis, UCP1 up-regulation, and ECM development. In response to CM induction, eWATs also secreted inflammatory adipokines related to the metastatic ability of cancer, muscle atrophy, and vascularization (NGAL, CD54, IGFBP-2, etc). Our work demonstrated that the eWAT is a robust model for studying cachectic fat loss and the accompanying remodeling of adipose tissue. It is therefore a useful tool for future research exploring CAC physiologies and developing potential therapies.